Biotechnological advancement in isolation of anti-neoplastic compounds from natural origin: a novel source of L-asparaginase - Abhinav, S.; Abdul, A.K.; Sudhir et al., K.J. (Acta Biomedica Atenei Parmensis, 2010)
L-asparaginase catalyzes the hydrolysis of L-asparagine into aspartate and ammonia, which is used as an anti-neoplastic agent. Isolation of asparaginase from microorganisms may be cardinal for producing this anticancer agent at industrial level. A total of three hundred fungal isolates were screened for L-asparaginase production. These fungal isolates were growing on various fruits and vegetables. Among these, the Fusarium sp. isolate that was growing on green chilly showed highest enzyme production. This study may give an outstanding contribution for finding organisms with high yielding L-asparaginase. Fungal L-asparaginase is superior in terms of its eukaryotic origin that may be responsible for its lesser toxicity.